2020
DOI: 10.2147/ccid.s222051
|View full text |Cite
|
Sign up to set email alerts
|

<p>Does the Autophagy Related Gene 7 (ATG7) Have a Role in Non-Melanoma Skin Cancer?</p>

Abstract: Purpose: To evaluate the role of autophagy related gene 7 (ATG7) in non-melanoma skin cancer. Subjects and Methods: This retrospective and prospective case-control study was performed on 104 patients with non-melanoma skin cancer (NMSC) in addition to 20 apparently healthy subjects matched for age and sex as a control group. Multiple skin biopsies were taken for immunohistochemical evaluation of ATG7 expression. Results: Both epithelial and stromal ATG7 were expressed in all participants while all patients sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Numerous investigations have indicated that oncogenic lncRNAs that function as ceRNAs are required for promoting autophagy in HCC. For example, autophagy-related genes 3, 5, 7, and 12 ( ATG3 , ATG5 , ATG7 , and ATG12 , respectively) are major regulators of the induction of autophagosome formation[ 41 - 43 ]. The lncRNA PVT1 promotes autophagy in HCC by enhancing ATG3 expression by sponging miR-365[ 44 ].…”
Section: Role Of Lncrnas As Cernas In Hccmentioning
confidence: 99%
“…Numerous investigations have indicated that oncogenic lncRNAs that function as ceRNAs are required for promoting autophagy in HCC. For example, autophagy-related genes 3, 5, 7, and 12 ( ATG3 , ATG5 , ATG7 , and ATG12 , respectively) are major regulators of the induction of autophagosome formation[ 41 - 43 ]. The lncRNA PVT1 promotes autophagy in HCC by enhancing ATG3 expression by sponging miR-365[ 44 ].…”
Section: Role Of Lncrnas As Cernas In Hccmentioning
confidence: 99%
“…On a common level, autophagy shows up basic to preserve both cellular homeostasis (through the expulsion of harmed protein and organelles) and giving a survival component for cells amid a push [4] . Subsequently, autophagy is associated with different pathologies, such as cancer, neurodegenerative disease, and inflammatory bowel disorders [5] . The skin serves as the primary line of defense against numerous distinctive environmental insults; however, the impact of autophagy on the pathogenesis of skin disorders was not adequately studied [6] .…”
Section: Introductionmentioning
confidence: 99%